Relationship of Teeth Brushing Habits with Dental Caries Incidence in 1st and 2nd Graders Students in State Elementary Schools No. 057205 Stabat Lama Kabupaten Langkat - Nilawati, Srinur (Jurnal Kesehatan Langkat Berseri (JURKESLASER), 2021)
The main health problems in the child’s mouth cavity is dental caries. The prevalence of dental caries tends to increase 60%-80%. The purpose of this study was to determine whether tooth brushing habit, how to brush, time to brush, frequency to brush the SDN No. 057205 Stabat Lama Kecamatan Stabat Kabupaten Langkat Tahun 2020. Using method of quantitative with cross sectional approach. Using proportionate random sampling technique in children 6-7 years old or grades 1-2. Atotal of 74 childrent. The instrumen used in the children, form of quetionnaries, observation of caries examination. The results of the analysis used chi square at α < 0,05. Results showed analysis there is not significant corelation between the independent variable it’s a toot brushing habit of children with dependent variable is dental caries, having p value = 0,346. This study is expected tobe referency for further research.